Morphology of arthropods discovered in pitchers of Nepenthes at Aceh Singkil District, Indonesia - MHD. RAFI’I MA’ARIF TARIGAN; MUHAMMAD FAISAL; KARTIKA MANALU; KHAIRUNA KHAIRUNA; EFRIDA PIMA SARI TAMBUNAN; RAHMADINA RAHMADINA; HUMAIROH ASY’ARI; YUSRAN EFENDI RITONGA (Society for Indonesian Biodiversity, 2024)
Abstract. Tarigan MRM, Faisal M, Manalu K, Khairuna, Tambunan EPS, Rahmadina, Asy’ari H, Ritonga YE. 2024. Morphology of arthropods discovered in pitchers of Nepenthes at Aceh Singkil District, Indonesia. Biodiversitas 25: 2888-2900. Nepenthes plants create unique microhabitats and are home to diverse arthropod communities. These plants, known for their complex and specialized structures, attract various species of arthropods and contribute to the region's biodiversity. The study of arthropod morphology is critical to understanding the complex interactions within these microhabitats as well as broader ecosystem dynamics. Although this plant has great ecological importance and conservation significance, detailed morphological studies of the arthropods living on it are still rare. This study aimed to identify the families of arthropods trapped in the upper and lower pitchers of Nepenthes. This study used descriptive methods to reveal the morphology of arthropods found in Nepenthes pitchers in Aceh Singkil District, Indonesia. Arthropods were obtained from the upper and lower pitchers of N. ampullaria, N. gracilis, N. mirabilis, N. rafflesiana, N. reinwardtiana, N. x hookeriana, and N. x trichocarpa. Samples were obtained through direct observations conducted between October to December 2023. The results showed the presence of arthropod families, namely Culicidae, Formicidae, Gryllidae, Calliphoridae, Coccinellidae, Curculionidae, Rhyaparochromidae, Blattellidae, Salticidae, and Araneidae. However, Culicidae and Formicidae were observed to be the most abundant and Gryllidae was observed to be the least abundant. A mutualistic symbiosis was established, in which ants used the tendrils of Nepenthes to lay eggs and collected nectar generated by the honey glands, while the egg-laying process helped in the breakdown of the pitcher. This discovery suggests that the plants provided a habitat for Culicidae and a conducive environment for Formicidae larvae. However, Araneidae, Rhyparochromidae, Salticidae, Curculionidae, and Coccinellidae are not attracted to petals and peristomes. Gryllidae and Blattellidae were present in Nepenthes pitchers as a result of their close association with the plant and UV color-trapping mechanism. The study of the morphology of arthropods found in Nepenthes pitchers has several overall implications. First, it contributes to our understanding of ecological interactions in Nepenthes plants, providing insight into predator-prey dynamics, nutrient cycling, and plant evolution. Second, it underscores the importance of Nepenthes plants as a microhabitat that supports diverse arthropod communities, and highlights the ecological role of arthropods in nutrient-poor environments. This research also informs conservation efforts, emphasizing the need to protect Nepenthes plant habitat to maintain biodiversity.